2022
DOI: 10.1088/1674-1056/ac615e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spatial heterogeneity on level of rejuvenation in Ni80P20 metallic glass

Abstract: Understanding the relation between spatial heterogeneity and structural rejuvenation is one of the hottest topics in the field of metallic glasses (MGs). In this work, molecular dynamics (MD) simulation was implemented to discover the effects of initial spatial heterogeneity on the level of rejuvenation in the Ni80P20 MGs. For this purpose, the samples were prepared with cooling rates of 1010-1012 K/s to make glassy alloys with different atomic configurations. Firstly, it was found that the increase in the coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…32 It is reported that the P atoms act as the solute constitute, prohibiting the significant formation of P-P bonds in the atomic configuration. 32 As can be observed, the main MRO peak is created in the range of 0. After the initial characterization of monolithic samples, the nanomechanical behavior of MG nanolaminates was studied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…32 It is reported that the P atoms act as the solute constitute, prohibiting the significant formation of P-P bonds in the atomic configuration. 32 As can be observed, the main MRO peak is created in the range of 0. After the initial characterization of monolithic samples, the nanomechanical behavior of MG nanolaminates was studied.…”
Section: Resultsmentioning
confidence: 99%
“…For monolithic Ni 80 P 20 MG, the Ni-P (0.215 nm) and Ni-Ni (0.262 nm) pairs are responsible for the formation of SRO peak in the PDF analysis. 32 It is reported that the P atoms act as the solute constitute, prohibiting the significant formation of P-P bonds in the atomic configuration. 32 As can be observed, the main MRO peak is created in the range of 0.39–0.64 nm, showing that the variety of connection type of SRO clusters is much higher than that detected in Cu 60 Zr 40 MG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation